2019
DOI: 10.1111/imr.12733
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of B cell fate and function during an immune response

Abstract: Summary The humoral immune response requires coordination of molecular programs to mediate differentiation into unique B cell subsets that help clear the infection and form immune memory. Epigenetic modifications are crucial for ensuring that the appropriate genes are transcribed or repressed during B cell differentiation. Recent studies have illuminated the changes in DNA methylation and histone post‐translational modifications that accompany the formation of germinal center and antibody‐secreting cells durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 100 publications
(181 reference statements)
1
18
0
Order By: Relevance
“…6b, c). This is interesting given recent data showing a role for H3K27me3 in regulating germinal B cell responses (31). As seen in the naïve state, CD4 + T cells harbouring a high amount of the Kdm6b hairpin had an associated higher frequency of activated CD4 + T cells compared to those harbouring the Luciferase hairpin ( Fig.…”
Section: Kdm6b Knockdown Results In Dysregulation Of An Influenza-spesupporting
confidence: 50%
“…6b, c). This is interesting given recent data showing a role for H3K27me3 in regulating germinal B cell responses (31). As seen in the naïve state, CD4 + T cells harbouring a high amount of the Kdm6b hairpin had an associated higher frequency of activated CD4 + T cells compared to those harbouring the Luciferase hairpin ( Fig.…”
Section: Kdm6b Knockdown Results In Dysregulation Of An Influenza-spesupporting
confidence: 50%
“…Higher levels of 5hmC prohibit cell division by maintaining cells in G1 for a longer period 10 , thus directly contributing to the balance between cell proliferation and apoptosis. Recent studies on 5hmC also revealed the complexes that form between transcription factors and epigenetic regulators during B-cell differentiation 11,12 , suggesting a potential role of 5hmC in B-cell malignancies. Therefore, profiling genome-wide 5hmC could provide insights on direct epigenetic landscape and adds additional value to the epigenetic modifications between DLBCL and FL.…”
Section: Introductionmentioning
confidence: 99%
“…CMV is known to challenge the immune system, altering the immune response to other pathogens (85). Both EBV and CMV cause a redistribution in B-cell subsets (86)(87)(88). Herpes viruses like EBV and CMV causing systemic infection of the immune system and the lifelong survival within the host with transient virus reactivation from time to time-going most often completely unnoticed and without any clinical symptoms (74, 89-96) -, are expected to leave an imprint on the immune system because of their lifelong infection of that same system.…”
Section: Discussionmentioning
confidence: 99%